The place and time of drugs - Duff, Cameron (Elsevier BV, 2014)
‘Context’ is one of the most enduring analytical devices in social science accounts of alcohol and other drug (AOD) use, although its elaboration tends to emphasise macro-structural processes (like economic change, law enforcement, health policy, racism or stigma) at the expense of more finely-grained understandings of the place and time of consumption. Drawing on Gilles Deleuze's notion of the assemblage, and its reception in recent critical geographies of AOD use, I will characterise context as an assemblage of social, affective and material forces. Such a characterisation is not indifferent to the range of structural forces that are often understood to mediate AOD use. Rather, it is concerned to document how these forces actually participate in the modulations of consumption. The assemblage will thus be construed in ways that align context with the ‘real conditions’ (place and time) of drug use. I will develop this argument by way of a case study drawn from a recent qualitative study of the social contexts of methamphetamine use in Melbourne. My goal is to document the ways ‘context’ is produced in the activity of drug use, and how ‘context’ so constructed, comes to modulate this use. By contrasting traditional approaches to the analysis of context with methods borrowed from Deleuze, I aim to transcend structural understandings of context in order to clarify the active, local and contingent role of contexts in the mediation of what bodies do ‘on’ and ‘with’ drugs.